Pengaruh Kompetensi Pegawai Terhadap Efektivitas Pelayanan Melalui Sistem Informasi Garut Satu Data Sebagai Variabel Mediasi (Studi Pada Diskominfo Kabupaten Garut) - Jamiat Romdoni; Gugun Geusan Akbar; Aceng Ulumudin (Public Inspiration : Jurnal Administrasi Publik, 2026)
The effectiveness of public services in the era of digital bureaucracy requires the simultaneous readiness of human resource capacity and the reliability of technological instruments. However, the implementation of data governance integration through the Garut One Data Information System at the Communication and Informatics Service (Diskominfo) of Garut Regency has not been fully optimal in boosting service performance in the field. This study aims to comprehensively analyze the influence of employee competency on public service effectiveness through the Garut One Data Information System as a mediating variable. This quantitative study used a descriptive-verificative design with a total sampling technique of 53 officials at Diskominfo Garut Regency. Primary data collection was conducted using a closed questionnaire instrument and analyzed using Variance-Based Structural Equation Modeling (VB-SEM) with the help of SmartPLS software. The structural testing results revealed a theoretical anomaly in the form of a full mediation phenomenon. Partially, employee competency was proven to have no significant direct effect on public service effectiveness. However, employee competency has a highly significant positive effect on the implementation of the information system, which in turn strongly boosts public service effectiveness. The conclusion of this study confirms that the high internal capacity of the apparatus is latent and will only manifest into excellent service when actualized through the reliability of digital platforms. The practical implication of these findings recommends the need for policy integration that synergizes the strengthening of employee data literacy with the simultaneous maintenance of information systems.